Prevalence and genotype distribution of caprine papillomavirus in peripheral blood of healthy goats in farms from three European countries - Cutarelli, Anna; De Falco, Francesca; Cuccaro, Bianca; Milićević, Vesna; Kureljušić, Branislav; Bojkovski, Jovan; Cerino, Pellegrino; Perillo, Antonella; Marica, Raluca; Catoi, Cornel; Roperto, Sante (Frontiers in Veterinary Science, 2023)
Caprine papillomaviruses (ChPVs, Capra hircus papillomaviruses) were detected and quantified for the first time using droplet digital polymerase chain reaction (ddPCR) in blood samples of 374 clinically healthy goats from farms located in Italy, Romania, and Serbia. Overall, ddPCR revealed ChPV DNA in 78 of the 374 examined samples, indicating that approximately 21% of the goats harbored circulating papillomavirus DNA. In particular, in Italian goat farms, ChPV genotypes were detected and quantified in 58 of 157 blood samples (~ 37%), 11 of 117 samples from Serbian farms (~ 9.4%), and 9 of 100 from Romanian blood samples (9%). Blood samples from Italian goat farms showed a high prevalence of ChPV1, which was detected in 45 samples (28.6%). The ChPV2 genotype was detected in 13 samples (~ 8.3%). Therefore, significant differences in prevalence and genotype distributions were observed. On Serbian and Romanian farms, no significant differences were observed in the genotype prevalence of ChPVs. Molecular findings are consistent with ChPV prevalence, characterized by a territorial distribution similar to that of papillomaviruses in other mammalian species. Furthermore, this study showed that ddPCR is a very sensitive and accurate assay for ChPV detection and quantification. The ddPCR may be the molecular diagnostic tool of choice, ultimately providing useful insights into the molecular epidemiology and field surveillance of ChPV.